The effects on oxidative aging, physical and flow properties of Agbabu natural bitumen modified with silver nanoparticles. Issue 6 (June 2020) - Olabemiwo, Ojeyemi M.; Lateef, Agbaje; Agunbiade, Foluso O.; Akanji, S.B.; Bakare, Hassan O.
Abstract: The quest for improvement in service life and performance of road pavement via reduction of oxidative aging failure of bitumen, led us to the investigation of novel application of Silver nanoparticles (AgNPs) as potential anti-oxidative material for Agbabu natural bitumen (ANB). The raw ANB was purified to form the base and the base modified in a stainless reactor using AgNPs via melt blend technique at temperature of 120 °C under stirring at 1200rpm. The proportions of AgNPs used for the modification were 1.5, 3.0 and 4.5 wt% and long-term aging was thermally simulated on the base and modified base samples at 60 °C. The aged samples were then subjected to Fourier Transform Infrared (FTIR) Spectroscopic Analysis to study the changes in the size of the peaks of the oxidation-related compounds. Physical and flow parameters (PFPs) of the base and modified base samples were characterized using softening point temperature, kinematic viscosity, penetration index, flash and fire points, penetration, kinematic viscosity and Oscillatory disc Rheometer (ODR) test. FTIR analysis showed that the AgNPs incorporation into ANB at 1797 cm −1, 1217 cm −1, 1300 cm −1 and 1097 cm −1 in the spectrum of the base sample. The sulphoxide peaks at 1031 cm −1 was completely obliterated. There was progressive reduction in the area of the carbonyl peak at 1693 cm −1 implying progressive lowering of the carbonyl index value with increasing in the amount of AgNPs used in the modification. These changes are attributable to the anti-oxidative potential of the AgNPs. The mechanism of the anti-oxidative effect of AgNPs is proposed to be due to scavenging of the free radical produced in the oxidation process. The values of softening point temperature, kinematic viscosity, penetration index, and flash and fire points increased while that of penetration and specific gravity reduced as the quantity of AgNPs in the base increased. The ODR test showed that, the modified samples compared to base sample at lower and higher road pavement temperatures are less prone to fatigue cracking and rutting, respectively. Thus, this study provides preliminary information about the novelty of AgNPs as potential antioxidant for improving the durability/performance of bitumen in pavements. Abstract : Nanotechnology, Physical Chemistry, Natural bitumen; Carbonyl and sulphoxide peaks; Silver nanoparticles; Physical and flow parameters; Antioxidants; Ageing